Long-term outcomes of acute kidney injury in acute decompensated heart failure: identifying true cardiorenal syndrome and unveiling prognostic significance - Peerapat Thanapongsatorn; Atiwat Tanomchartchai; Jarin Assavahanrit (The Korean Society of Nephrology, 2024)
Background Cardiorenal syndrome (CRS) type 1 defined as acute kidney injury (AKI) in acute decompensated heart failure (ADHF), is complicated due to diverse definitions. Recently, a more precise CRS type 1 definition was proposed, mandating concurrent AKI and signs of unimproved heart failure (HF). Our study explores the incidence, predictors, and long-term outcomes of AKI in ADHF under this new definition. Methods A prospective observation study of ADHF patients categorized into the CRS type 1, pseudo-CRS, and non-AKI groups, followed for 12 months. CRS type 1 involved AKI with clinical congestion, while pseudo-CRS included AKI with clinical decongestion (clinical congestion score <2). The primary outcome was a 1-year composite of mortality or HF rehospitalization. Results Among 250 consecutive ADHF patients, 46.0% developed CRS type 1; chronic kidney disease (CKD) and blood urea nitrogen were significant risk factors (odds ratios, 1.37; p = 0.002 and OR, 1.05; p < 0.001, respectively). The CRS type 1 group exhibited shorter times to AKI development and peak serum creatinine than the pseudo-CRS group (1 day vs. 4 days and 2 days vs. 4 days, respectively). At 12 months, composite outcomes of mortality or HF rehospitalization and CKD progression were significantly higher in the CRS type 1 group than in the pseudo-CRS and non-AKI groups (63.5% vs. 31.7% vs. 36.1%, p < 0.001; 28.1% vs. 16.2% vs. 11.4%, p = 0.024, respectively). Conclusion Distinguishing between CRS type 1 and pseudo-CRS is vital, highlighting significant disparities in short-term and long-term outcomes. Notably, pseudo-CRS exhibits comparable long-term cardiovascular and renal outcomes to those without AKI.